GAMBARAN DUKUNGAN KELUARGA PADA PASIEN TUBERKULOSIS (TB) PARU DALAM MENJALANI PENGOBATAN DI WILAYAH KECAMATAN WONOGIRI - Solikhah, Maula Mar'atus; Rusmillah, lisa Ari; Murharyati, Atiek; Fitriyani, Noor (Universitas Kusuma Husada Surakarta, 2022)
Tuberculosis (TB) is an infectious disease, which is mostly caused by the bacteria Mycobacterium tuberculosis. One of the factors that influence TB patients in undergoing treatment is family support. The purpose of this study was to determine the description of family support obtained by pulmonary tuberculosis (TB) patients. This research was conducted in Wonogiri District. The research design used a descriptive survey. Sampling with total sampling, as many as (n = 59) in TB patients who are undergoing treatment. The research tool used a family shaman questionnaire. The results showed that good family support for 30 respondents (50.8%) was almost the same as the number of poor family support, namely 29 (49.2%). Suggestions for further research recommend empowering families in providing family support in the form of emotional support to help TB patients in the treatment program